Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/s12630-015-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

Intubation with VivaSight or conventional left-sided double-lumen tubes: a randomized trial

Abstract: Introduction Double-lumen endotracheal tubes (DLTs), which are commonly used for single-lung ventilation during surgery, are difficult to insert. In addition, they often move during surgical lung manipulation which can cause lifethreatening complications. Flexible bronchoscopy is used routinely to establish and confirm proper DLT placement. The newly designed VivaSight DLT has an integrated camera, allowing continuous visualization of its position in the trachea. We hypothesized that the time to intubation usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
52
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 24 publications
4
52
1
Order By: Relevance
“…The main weakness of this study is the fact that the intubating anaesthesiologist was not blinded to the device used. A similar recent study found that the mean (SD) intubating time with the VivaSight DL was significantly shorter than a conventional DLT (63 (58) s vs. 94 (84) s, p = 0.03), the latter value for conventional DLT being much shorter [14] than measured in our study. We attribute this difference to the time for preparation and use of the fibreoptic bronchoscope.…”
Section: Discussionsupporting
confidence: 63%
“…The main weakness of this study is the fact that the intubating anaesthesiologist was not blinded to the device used. A similar recent study found that the mean (SD) intubating time with the VivaSight DL was significantly shorter than a conventional DLT (63 (58) s vs. 94 (84) s, p = 0.03), the latter value for conventional DLT being much shorter [14] than measured in our study. We attribute this difference to the time for preparation and use of the fibreoptic bronchoscope.…”
Section: Discussionsupporting
confidence: 63%
“…As discussed in our paper, 1 positioning the VivaSight DLT 34 sec faster than positioning a conventional doublelumen tube is of marginal clinical importance. Then again, faster insertion is consistent with the fact that the tube is easy to use.…”
Section: To the Editormentioning
confidence: 82%
“…Since Vivasight-DL is now available in sizes 35, 37, 39, and 41 Fr, we think that the Brodsky criteria [2] could be helpful in selecting the appropriate size of a double-lumen tube (DLT) for a specific patient. However, we often tend to choose a smaller DLT, as using 35 Fr DLTs produces similar outcomes to using larger sizes [3].…”
Section: Placement Of Vivasight Double-lumen Tube -A Replymentioning
confidence: 99%
“…They also comment that time to intubation in the control group included the time to use the FOB, leading to a particularly prolonged 'intubation time'. In comparison, Schuepbach et al [3] found that the mean time to correct placement by auscultation for the VivaSight vs conventional DLT was 63 s vs 97 s.…”
mentioning
confidence: 96%
See 1 more Smart Citation